2010
DOI: 10.1016/j.watres.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Bio-diatomite dynamic membrane reactor for micro-polluted surface water treatment

Abstract: Keywords:Bio-diatomite dynamic IntroductionThe dynamic membrane technology for wastewater treatment has gained great attention in recent years due to its cost-effective membrane module, reduced energy consumption and high effluent quality. Therefore, it is considered as a substitute to the conventional membrane bioreactor (MBR) (Kiso et al., 2004;Gander et al., 2000;Chu and Li, 2006). Dynamic membrane is formed on the underlying support mesh when filtering a solution containing fine particles, thus is also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 20 publications
2
35
1
1
Order By: Relevance
“…The major quality are summarized in Table 1. This kind of water is similar to polluted raw water in Eastern China according to the on-the-spot investigation and related literature (Chu et al, 2010;Feng et al, 2013;Zhang et al, 2013).…”
Section: Characteristics Of Polluted Raw Watermentioning
confidence: 85%
See 1 more Smart Citation
“…The major quality are summarized in Table 1. This kind of water is similar to polluted raw water in Eastern China according to the on-the-spot investigation and related literature (Chu et al, 2010;Feng et al, 2013;Zhang et al, 2013).…”
Section: Characteristics Of Polluted Raw Watermentioning
confidence: 85%
“…Thereinto, the pollution of drinking water source directly threatens the drinking water safety (Chu et al, 2010;Zhang et al, 2013). For example, the major pollutants such as ammonia and organics existing in water could complicate the chlorination process and form disinfection byproducts (Chowdhury et al, 2009;Benner et al, 2013;Han et al, 2013), which would cause health problems to people.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the latter mechanism was absent for sulfamethoxazole as this compound is rather hydrophilic. Chu et al (2010) investigated the feasibility of treating micro polluted surface water for drinking water production with a bio-diatomite dynamic membrane reactor (BDDMR) at a laboratory-scale-discontinuous-flow mode. Results indicated that the BDDMR was effective in removing trihalomethanes' formation potential (THMFP) at a hydraulic retention time (HRT) of 3.5 h due to its high concentrations of mixed liquor suspended solids (MLSS) and mixed liquor volatile suspended solids (MLVSS).…”
Section: Control Technologymentioning
confidence: 99%
“…Compared with traditional membranes, inexpensive materials, high filtration flux, better filtration performance, and easy formation from various substances are very attractive features of dynamic membrane [4,5]. Therefore, it is considered as a substitute for the conventional membrane reactor [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al [7,16] used biodiatomite dynamic membrane reactor for micro-polluted surface water treatment, the results showed it is advantageous in high filtration flux, long filtration time, and excellent solid-liquid separation capacity, and Pollutants could be removed effectively by the reactor. But, they believed that the removal of pollutants was mainly ascribed to microbial degradation and the membrane alone; PAC-diatomite absorption was much less effective in removing pollutants.…”
Section: Introductionmentioning
confidence: 99%